1986
DOI: 10.1002/hed.2890080308
|View full text |Cite
|
Sign up to set email alerts
|

Pain in the head and neck cancer patient: Changes over treatment

Abstract: The incidence, severity, and location of pain was evaluated in 30 head and neck cancer patients prior to treatment after the first phase of their treatment and upon the completion of treatment. The incidence of pain was relatively high (40%-70%) and tended to increase slightly over treatment. Patients having advanced disease (stage III or IV) had a higher incidence of pain. Pain severity ratings were stable over treatment. Pain was located close to tumor or incision sites, and a trend for patients to report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 11 publications
0
73
2
Order By: Relevance
“…The last of these remains one of the more significant challenges to effective treatment in the long term, as the overall survival rates for SCCHN have not radically improved since the 1970s [3,15,16,22,23,24,25,26,27,28]. In addition, pain remains a common symptom in SCCHN patients and suffering has been underevaluated in patients with primary stage SCCHN [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The last of these remains one of the more significant challenges to effective treatment in the long term, as the overall survival rates for SCCHN have not radically improved since the 1970s [3,15,16,22,23,24,25,26,27,28]. In addition, pain remains a common symptom in SCCHN patients and suffering has been underevaluated in patients with primary stage SCCHN [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…1 Head and neck cancer may lead to severe pain complaints. 2,3 Besides certain specific symptoms like hoarseness and swallowing complaints, the symptoms of the disease are to a considerable extent determined by pain. The rich innervation of the head and neck area by the sensory cranial nerves V, IX, and X and the cervical spinal nerves C1-C4 contribute greatly.…”
mentioning
confidence: 99%
“…2,3,8,9 Because pain may be the first symptom of recurrent disease, we have retrospectively analyzed the importance of pain assessment and the diagnosis of tumor recurrence with special reference to referred pain.…”
mentioning
confidence: 99%
“…A higher incidence of pain was noted in more advanced disease i.e. stages III or IV (Keefe et al, 1986). A recent study showed that a third of patients who attend head and neck cancer outpatients had pain from any cause within the previous seven days, with over two-thirds of those having severe pain (Williams et al, 2010).…”
Section: Prevalence Of Painmentioning
confidence: 99%
“…The prevalence of pain at diagnosis of head and neck cancers vary from 40% to 84% (Keefe et al, 1986;Chaplin, 1999;Epstein, 1993;Saxena et al, 1995). A higher incidence of pain was noted in more advanced disease i.e.…”
Section: Prevalence Of Painmentioning
confidence: 99%